The word” love", the national-cultural characteristics of the paremas related to the concept of meanings - Gulnoza Turdieva Saifullayevna (Global Scientific Publishing, 2023)
This article will talk about one of the interesting scientific areas in World linguistics, the lexical-semantic analysis of phraseologisms, in particular phraseological phrases related to the concept of “Love”, national-cultural characteristics. In Uzbek linguistics, on the basis of the meaning of phraseologisms, their classification according to their lexical and semantic characteristics, phrases related to the expression of the concept of “love” are grouped on the basis of a certain system of coloro-coloring of phrases, expressions that manifest subtleties of meaning in them, the concept of “love” and concepts
Keywords: linguomadanium; concept; parema; phraseological unit